Recruitment, employment, retention and the minority teacher shortage - Ingersoll, Richard; May, Henry; Collins, Gregory (Education Policy Analysis Archives, 2019)
This study examines and compares the recruitment, employment, and retention of minority and nonminority school teachers over the quarter century from the late 1980s to 2013. Our objective is to empirically ground the ongoing debate regarding minority teacher shortages and changes in the minority teaching force. The data we analyze are from the National Center for Education Statistics’ nationally representative Schools and Staffing Survey (SASS) and its longitudinal supplement, the Teacher Follow-up Survey (TFS). Our data analyses document the persistence of a gap between the percentage of minority students and the percentage of minority teachers in the US. But the data also show that this gap is not due to a failure to recruit new minority teachers. In the two decades since the late 1980s, the number of minority teachers almost doubled, outpacing growth in both the number of White teachers and the number of minority students. Minority teachers are also overwhelmingly employed in public schools serving high-poverty, high-minority and urban communities. Hence, the data suggest that widespread efforts over the past several decades to recruit more minority teachers and employ them in disadvantaged schools have been very successful. But, these efforts have also been undermined because minority teachers have significantly higher turnover than White teachers and this is strongly tied to poor working conditions in their schools.